CRITICAL DISCOURSE ANALYSIS OF THE REPRESENTATION OF SANTRI IDENTITY IN TAJ YASIN’S DEBATE SPEECHES DURING THE 2024 CENTRAL JAVA GUBERNATORIAL ELECTION - Adhitya Sandy Wicaksono; Fitriyah Fitriyah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Identity politics rooted in pesantren culture plays a significant role in electoral contestation in Central Java; however, studies examining how santri identity is discursively represented, particularly within candidate debate forums, remain limited. This research aims to analyze the construction of santri identity in three debate speeches delivered by Taj Yasin during the 2024 Central Java gubernatorial election using Norman Fairclough’s Critical Discourse Analysis (CDA) framework. The data consist of debate transcripts, which are examined through three analytical levels: textual analysis, discourse practice, and sociocultural practice. The findings reveal that santri identity is constructed through the strategic use of religious and pesantren-specific diction such as nglakoni, ngopeni, and akhlaq, as well as through narratives of moral exemplarity and genealogical references to respected religious figures, including the teachings of K.H Maimoen Zubair. This identity construction is further reinforced by visual performativity, particularly the consistent use of sarong and black cap throughout the debates, and by framing pesantren values as the normative foundation for policy arguments in education, sharia-based economics, environmental issues, and social development. At the sociocultural level, the construction of santri identity resonates strongly with the religious and pesantren-oriented character of Central Javanese society, functioning as both symbolic capital and a political communication strategy. This study concludes that santri identity operates not merely as a personal attribute but as a deliberate discursive strategy that integrates language, symbols, and cultural values to establish political legitimacy in the electoral arena.